Structure and Interrelations of the State System of Innovation Management at the Federal and Regional Levels - Petrovich, Garnov Andrey; Alekseevna, Prodanova Natalia; Yuryevna, Garnova Victoria; Vladimirovna, Shabaltina Larisa; Ivanovna, Zatsarinnaya Elena ,; Vitalievna, Panferova Liya (International Journal of Psychosocial Rehabilitation, 2020)
requires an analysis of the state of the innovation environment also based on the use of General theoretical principles of consistency, complexity, normativity, continuity, program-target orientation, adaptability and quantitative measurability. The article reveals the features of the functioning of regional innovation systems, describes the indicators and features that determine the specifics of each regional innovation system, and considers the main methodological approaches and their general characteristics, special and particular theoretical principles of the formation and functioning of regional innovation systems. The essence and possibility of applying general theoretical principles and indicators of state statistical reporting to analyze the innovative position of regions are revealed.